Meningkatkan Interaksi Sosial Anak Melalui Metode Kerja Kelompok di Kelompok B TK Karya Thayyibah II Nupa Bomba Kecamatan Tanantovea - Hj. Aspiani, Hj. Aspiani (Bungamputi, 2014)
ABSTRACT The problem in this study is whether the child's social interaction skills can be enhanced through group work method in group B TK Karya Thayyibah II Numpa Bomba district Tanantovea ? Then the purpose of this research is to improve the child's social interaction skills through group work method in group B TK Karya Thayyibah II Numpa Bomba district Tanantovea . The design of this research study Kemmis and Mc . Taggart consisting of two cycles . Where on each cycle of meetings held three times in the classroom and each cycle consists of four stages: planning , implementation, observation, and reflection. The experiment was conducted in TK Karya Thayyibah II Numpa Bomba district Tanantovea , as many as 17 children consisted of 9 boys and 8 girls . Data were collected by using observation and documentation analyzed descriptive . Data collected prior to the action capabilities in berbgai with friends category SB of 5.88 % , B 11.76 % , C 29.41 % , and 52.94 % K , then the ability of children loving friend category SB of 5.88 % , B 11 , 76 % , C 35.29 % , K 47.05 % , and the child's ability to invite friends to learn the category SB of 5.88 % , B 5.88 % , C 41.17 % , K 57.05 % . After the action is taken , the results of this study it can be concluded that through group work method can improve the child's social interaction skills , proven no upgrades from the first cycle to the second cycle in a child's ability to share with friends very well and good categories from 58.81 % to 82 , 34 % ( 23.53 % ) , then love is very good friends and good categories from 41.16 % to 76.46 % ( 35.3 % ) , and the latter referring friends beajar excellent and good categories from 41.16 % to 76.46 % ( 35.3 % ) . In general, an increase of all abilities are measured